Analisa UI dalam Perancangan Aplikasi Pemesan Kue “Cakeland” dengan Metode SEQ - Putra, I Putu Dana; Suputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
UI and UX are two inseparable things, these two things are the key to the success of a digital product which is a website or mobile application. UI or User Interface is conceptually part of UX or User Experience. Because if the UI owned by a digital product has a very good design, function, and ease of use, it will also have an impact on the UX or user experience it has. Including if the UI is immature and very difficult to use, it will make the user experience not optimal. This study was made with the aim of analyzing the UI quality of “Cakeland” as a Cake Ordering Application. To measure the quality of the UI that is owned here will be done using the SEQ method or Single Ease Question and tested in a tool called Maze. Quality evaluation on the usability aspect will be carried out later to determine whether the UI owned by the "Cakeland" application is feasible or not and whether the "Cakeland" application is feasible to be improvised in further research.